Potential Inclusion of Multiple Intelligences in Jordanian EFL Textbooks: A Content Analysis - Taghrid Ahmad Al-Omari; Ruba Fahmi Bataineh; Oqlah Mahmoud Smadi (Bellaterra Journal of Teaching & Learning Language & Literature, 2015)
This study examines the potential incorporation of the principles of Multiple Intelligences Theory in the Jordanian EFL textbooks.  More specifically, it reports on a content analysis of Action Pack textbooks for the first-, fourth-, eighth- and eleventh-grades by means of content analysis. The findings reveal that the moral, existential and spiritual intelligences are not incorporated in the activities of the textbooks under study; the verbal/linguistic, intrapersonal and spatial/visual intelligences are relatively more incorporated than other intelligences; and the inclusion of multiple intelligences is fairly unbalanced in the four textbooks.